Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1098/rsos.160855
|View full text |Cite
|
Sign up to set email alerts
|

State anxiety and emotional face recognition in healthy volunteers

Abstract: High trait anxiety has been associated with detriments in emotional face processing. By contrast, relatively little is known about the effects of state anxiety on emotional face processing. We investigated the effects of state anxiety on recognition of emotional expressions (anger, sadness, surprise, disgust, fear and happiness) experimentally, using the 7.5% carbon dioxide (CO2) model to induce state anxiety, and in a large observational study. The experimental studies indicated reduced global (rather than em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
35
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 56 publications
6
35
1
Order By: Relevance
“…Relatedly, a third aim was to examine whether levels of comorbid psychopathology were associated with emotion recognition performance. As well as including measures of alexithymia and ASD traits, we included depression, anxiety, and social anxiety due to their high co-occurrence with AN [8,32,45] and potential effects on social cognition [46][47][48][49][50][51]. We hypothesised that individuals with AN would be less accurate at recognising complex emotions compared to HCs, and that those recovered from AN would show intermediate levels of performance.…”
Section: Introductionmentioning
confidence: 99%
“…Relatedly, a third aim was to examine whether levels of comorbid psychopathology were associated with emotion recognition performance. As well as including measures of alexithymia and ASD traits, we included depression, anxiety, and social anxiety due to their high co-occurrence with AN [8,32,45] and potential effects on social cognition [46][47][48][49][50][51]. We hypothesised that individuals with AN would be less accurate at recognising complex emotions compared to HCs, and that those recovered from AN would show intermediate levels of performance.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research findings about the effects of generalized anxiety disorder (GAD) on emotion perception been varied and even contradictory. While some studies have linked GAD with lower emotion identification ability (Attwood et al, 2017) and selective attention to threat relative to controls, other studies have shown people with generalized anxiety symptoms have a lower threshold for emotion identification, that is, they perceive target emotions more quickly than non-anxious groups (Bradley, Mogg, White, Groom, & de Bono, 1999;Bui et al, 2017;Plana, Lavoie, Battaglia, & Achim, 2014). High trait anxiety has been linked to better facial recognition of fear specifically (Surcinelli, Codispoti, Montebarocci, Rossi, & Baldaro, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Experimental research has shown reduced emotion recognition accuracy and increased interpretation bias when state anxiety was heightened (Attwood et al, 2017).…”
Section: Limitationsmentioning
confidence: 99%
“…There is evidence to support that higher trait and state anxiety is associated with poorer emotion recognition (Blair et al, 2008;Attwood et al, 2017). Experimental research has shown reduced emotion recognition accuracy and increased interpretation bias when state anxiety was heightened (Attwood et al, 2017).…”
Section: Introductionmentioning
confidence: 99%